The Role of Anonymity in the Flaming Activity on YouTube in Malaysia - Lingam, Revathy Amadera; Aripin, Dr. Norizah (Universitas Semarang, 2019)
The term flaming refers to offensive language such as swearing, insults and hating comments. Anonymity renders an environment that encourages irresponsible acts by people to display offensive behaviors. The aim of this study is to examine the role of anonymity in the flaming activity in Malaysia. The Uses and gratification Theory was proposed in order to explain flaming and its relation to anonymity. In-depth interview was conducted with 10 flamers of YouTube and the data was analyzed thematically. The results concludes that most of the flamers kept their identity anonymous due privacy concerns and for the freedom of speech. The rest of the flamers used their real name as a form of publicity, identity defining and to boost their self-confidence. This study contributes practically in the enrichment of the data on flaming for the concerning parties such as Malaysian Communications and Multimedia Commission, and Cyber Security Malaysia.